SYNTHESIS, MOLECULAR MODELING, AND QUANTITATIVE STRUCTURE–ACTIVITY RELATIONSHIP STUDIES OF UNDEC-10-ENEHYDRAZIDE DERIVATIVES AS ANTIMICROBIAL AGENTS - Kumari, Manju; Narang, Rakesh; Nayak, Surendra Kumar; Singh, Sachin Kumar; Gupta, Vivek; Narasimhan, Balasubramanian (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In recent years, an increasing frequency and severity of antimicrobial resistance to different antimicrobial agents, demands new remedies for the treatment of infections. Therefore, in this study, a series of undec-10-enehydrazide derivatives were synthesized and screened for in vitro activity against selected pathogenic microbial strains. Methods: The synthesis of the intermediate and target compounds was performed by standard procedure. Synthesized compounds were screened for antimicrobial activity by tube dilution method. Molecular docking study of synthesized derivatives was also performed to find out their interaction with the target site of β-ketoacyl-acyl carrier protein synthase III, (FabH; pdb id:3IL7) by docking technique. Quantitative structure–activity relationship (QSAR) studies were also performed to correlate antimicrobial activity with structural properties of synthesized molecules. Results: Antimicrobial screening results showed that compound 8 having benzylidine moiety with methoxy groups at meta and para position and compound 16 having 3-chloro-2-(3-flourophenyl)-4-oxoazetidine moiety was found to be most potent. QSAR studies revealed the importance of Randic topology parameter (R) in describing the antimicrobial activity of synthesized derivatives. Molecular docking study indicated hydrophobic interaction of deeply inserted aliphatic side chain of the ligand with FabH. The N-atoms of hydrazide moiety interacts with Ala246 and Asn247 through H-bonding. The m- and p-methoxy groups form H-bond with water and side chain of Arg36, respectively. Conclusion: Compound 8 having benzylidine moiety with methoxy groups at meta and para position and compound 16 having 3-chloro-2-(3- flourophenyl)-4-oxoazetidine moiety was found to most potent antibacterial and antifungal compounds, respectively.